4x-3(6)=6-12

Simple and best practice solution for 4x-3(6)=6-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(6)=6-12 equation:



4x-3(6)=6-12
We move all terms to the left:
4x-3(6)-(6-12)=0
We add all the numbers together, and all the variables
4x-36-(-6)=0
We add all the numbers together, and all the variables
4x-30=0
We move all terms containing x to the left, all other terms to the right
4x=30
x=30/4
x=7+1/2

See similar equations:

| n=n+345 | | 25=4n−3 | | 8x-3=-16 | | -3(y/3+1)-2=4(1-y) | | v+-154=588 | | 4(-3)+7y=2 | | 18d-17d=13 | | –r-5=1–2r | | 8x+6=25 | | v+47=82 | | 4a+6=8a-6 | | 15/2x=6/x+9 | | h=6h+15 | | 2(x−4)(x+1)=0 | | -8x-4=4-5x | | X-0.12x=185 | | j+242=708 | | 5x+8(85-x)=500 | | (3x+x)/2=486 | | 4x+24-8×=2x | | 11x-6+134=180 | | c-9=62 | | 12x-(x+5)=10x-1 | | 3+^x-6=^x+9 | | 3y+2(y-4)=5(y-1)+2y+3 | | 7x+4/3=x+12 | | (x+1)(x+1)=xxx+29 | | 5x-2(x-1)+19)=(x-1) | | 5(-2x+7)=6x+3 | | x²-5x=6 | | 5x+3x+12=180, | | 6y-3(y+1)=2(y+3)+3 |

Equations solver categories